Formation of strength abilities in students of agricultural university - Antsyperov, Vladimir V.; Sychev, Pavel A.; Vlasova, Tatyana N.; Kozlova, Tatyana N.; Popova, Olga M. (Физическое воспитание и студенческий спорт)
Strength training at student age has a beneficial effect on physical condition and health and has its maximum impact at the end of puberty at the age of 16–22. Taking into account the insufficient strength training of student youth, the goal was set to attract 1st, 2nd and 3rd year students of the Volgograd State Agrarian University aged 17 to 22 years to participate in athletic sports within the framework of the curriculum and to assess the level of their strength preparedness after undergoing athletic training carried out on the basis of an individual approach that takes into account the initial level of strength qualities. After completing the classes, final competitions were held, the program of which included powerlifting exercises: barbell squats, bench press and deadlift. Based on the results, the level of strength readiness of 116 1st–3rd year students was compared and the impact of compulsory athletic training was assessed. The obtained results showed that the strength development of students increases from course to course, which is clearly expressed by the average total results of relative strength: the average coefficient according to the GL Points-IPF formula in the first year was 214.0 ± 6.4, in the second year it was already 219.2 ± 7.7, and on the third reached 237.6 ± 7.6 points, which is obviously due to the use of not only strength exercises, but also age related changes, characterized by an increase in muscle mass and its qualitative changes. It should be noted that the use of strength exercises to obtain a positive result requires a long time. It can be assumed that only by the end of the second year of study students begin to demonstrate an increase in strength and show fairly high results.